PENGEMBANGAN KAPITAL SOSIAL DALAM PENGELOLAAN BANK SAMPAH “CIBER” - Marcell Sinay; Triyanti Anugrahini (Indonesian Journal of Social Work, 2022)
The waste problem is one of the social issues faced by the community. In overcoming the waste problem, government encourages community participation in waste management, one of which is through the waste bank program. The CIBER Waste Bank is located in the Cilincing village, Cilincing district, North Jakarta. This study aims to describe the process of developing social capital that occurs in the CIBER Waste Bank. This study uses a qualitative approach, by conducting in-depth interviews with 7 informants selected through purposive sampling technique. The results of the study indicate that the development of social capital at the CIBER waste bank begins with opening initial contacts to coordinate, fulfill the requirements for cooperation, conduct socialization and direct invitation toward residents, as well as carry out previous joint activities. For efforts to develop social capital that has been formed, CIBER's strategy is to ensure a smooth payment process, meet operational needs in the field, share assistance, ensure a smooth waste transportation process, share information, ensure that waste sales run regularly, meet the volume of waste sales in large quantities, and ensure the quality of the waste being sold